Research publications and global manufacture of veterinary vaccines against avian influenza A (2019-2023) - Domínguez-Odio, Aníbal; Rodríguez-Martínez, Ernesto; Paneque Zayas, Mayelin; Cala-Delgado, Daniel Leonardo (Frontiers in Veterinary Science, 2025)
The characteristics of the avian influenza virus and its worldwide spread have led to intense and unprecedented scientific activity and industrial production for preventive veterinary vaccines. However, knowledge gaps remain regarding the best strategies to prevent epidemiological events in the future. In this context, the present study aimed to provide a global analysis on the scientific and industrial production of avian influenza type A vaccines for farm animals and pets during the period 2019 2023. The Scopus database was used as the primary source of information (12,162 keywords, 2,437 scientific articles, 659 academic journals, and 46 countries) for the academic analysis, while technical information posted on official institutional websites (136 commercial formulations, 24 vaccines manufacturers, and 17 countries) was collected to conduct the industrial analysis. 3,045, 25.0%) exhibited the highest levels of co-occurrence in the sciences; the journal Vaccine was the most productive in terms of articles (11.8%, 288/2,437), and the countries with the most publications were the USA (25.5%, 622/2,437) and China (23.1%, 564/2,437). The most internationally marketed vaccines were inactivated (86.0%, 117/136), avian (47.1%, 64/136), and combined (52.2%, 71/136) vaccines as well as those containing Newcastle antigens (38.0%, 27/71). In conclusion, the study demonstrated the fundamental role of classical production methods (based on the use of the whole pathogen) in avian influenza A research and the production of veterinary vaccines.